Between colour lines : interrogating the category ‘coloured’ in depictions of District Six in the work of five South African artists - Cupido, Cameron Amelia (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA(VA))--Stellenbosch University, 2018.